English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

x ^2 + 4 = 6x

I came up with....
x= -2 (+-) square root of 10

2007-05-06 12:19:23 · 5 answers · asked by confused 1 in Science & Mathematics Mathematics

5 answers

x = -b+/- sqrt(b^2-4ac) all over 2a
x = 3 +/- sqrt(5)

2007-05-06 12:25:04 · answer #1 · answered by Seth 2 · 0 0

x^2-6x+4=0
here, a=1
b=-6
c=-4
x= -b(+-)root overb^2- 4ac divided by2a
x=3(+-) square root of 13

2007-05-06 12:31:21 · answer #2 · answered by arun o 1 · 0 0

Quadratic Formula: x = (-b +/- sqrt(b^2 - 4ac))/(2a)

x = (6 +/- sqrt(36-4(1)(4)))/(2*1) = 6 +/- 2*sqrt(5)/2
x = 3 +/- sqrt(5)

2007-05-06 12:27:02 · answer #3 · answered by JaniesTiredShoes 3 · 0 0

The formula you are solving is
x² - 6x + 4 = 0

In the quadratic formula it starts out -b +- ...

So your -b value is 6.

.

2007-05-06 12:30:38 · answer #4 · answered by Robert L 7 · 0 0

x ^2 + 4 = 6x
x^2-6x+4=0

x= [6+/- sqrt(36-16)]/2
x= [6+/- 2sqrt(5)]/2
x= 3+sqrt5 or 3-sqrt5

2007-05-06 12:25:30 · answer #5 · answered by jaybee 4 · 0 0

fedest.com, questions and answers